Pengembangan Program Diniyah di MI Nurul Islam Petahunan Tahun Pelajaran 2024-2025: (Analisis Efektivitas Pembelajaran Diniyah Berbasis Formal) - Ni'mah Lailatul Mas'adah; Fahrun Nizma Furoidah (TARBAWIYAT, 2026)
Religious education plays an essential role in strengthening students' character and spiritual values. In addition to intracurricular Islamic education, schools require complementary programs that reinforce students' religious understanding. MI Nurul Islam Petahunan implements a Diniyah Program as a non-formal religious education program organized through a structured learning system resembling formal education, including scheduled classes, teacher journals, attendance records, and semester assessments. This study aims to analyze the development and effectiveness of the Diniyah Program for first-grade students and to identify the supporting and inhibiting factors affecting its implementation during the 2024–2025 academic year. This research employed a descriptive qualitative approach. Data were collected through observations, in-depth interviews, and documentation, and analyzed using an inductive qualitative technique. The findings indicate that the Diniyah Program has been implemented effectively through systematic planning, structured learning activities, and continuous evaluation. The program also contributes to strengthening students' religious knowledge, discipline, and learning participation. Supporting factors include teachers' commitment, adequate learning facilities, and parental support, whereas differences in students' abilities, limited instructional time, and low learning motivation among some students remain the primary obstacles. The study concludes that the structured implementation of a non-formal Diniyah Program can serve as an effective model for strengthening Islamic religious education in madrasah.